Evaluation of the health seeking practices among diabetics (>10 years of duration) in the field practice areas of government medical college, Amritsar - Soni, Anamika; Lal, Mohan; Deepti, Shyam Sunder; Singh, Tejbir; Kaur, Jasleen (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetes has become global issue due to premature illness and death due to its complications. Awareness about good health seeking practices are essential for prevention, early detection and management of diabetic complications. Objective of the study was to evaluate the health seeking practices among diabetics (>10 years of duration) in the field practice areas of Government Medical College, Amritsar. Methods: A community based cross-sectional study was conducted in rural and urban areas of district, Amritsar. A total of 200 diabetic patients who had diabetes equal to or more than 10 years of duration were interviewed using pretested and predesigned questionnaire. Data such collected was analysed at p<0.05. Results: Out of total 200 diabetic respondents, 50% (100) were from urban and 50% (100) were from the rural area. In both urban and rural areas, majority were literate i.e. 80% (161) and employed i.e. 51% (103). The mean age of diabetic respondents was 58.05 years with a male to female ratio of 1.1:1. The majority 82% (165) were diagnosed in the private sector and 99% (198) were on allopathic treatment. Oral hypoglycaemic agents were used by 77% (153) patients to manage their disease. 23% (45) were using both oral hypoglycaemic agents and insulin. About 48% (96) were monitoring their RBS regularly, 76% (151) were on regular treatment for diabetes and 55 (27%) were doing physical activity. Conclusions: Poor health seeking practices and less awareness about non pharmacological measures are main factors for development of complications among diabetics.